ปัจจัยที่กำหนดความสัมพันธ์ระหว่างราชอาณาจักรลาวกับสหภาพโซเวียตในทศวรรษ 1950 - วิลาวรรณ สายวังเฮอ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objective of this thesis is to examine factors instrumental in determining relations between the Kingdom of laos and the U.S.S.R in the 1950 s. It analyses the internal and external factors of the Kingdom of Laos that influenced its relations with the U.S.S.R Employing the concepts of "linkage politics" and "colonial imperialism", this study found that Laos s decision to establish ties with the Societ Union was based on several external factors, including the French-colonialism in Laos, the bi-polarity during the Cold War in which Laos sided with the United States, the foreign policies of the Soviet Union, China and North Vietnam toward the Kingdom of Laos. It also found that the Kingdom of Laos s internal political and economic factors forced its leaders to open door to the Socialist countries such as the U.S.S.R for economic and military assistances in order to cope with the country s problems.